2016
DOI: 10.18632/oncotarget.14330
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun-N-terminal phosphorylation regulates DNMT1 expression and genome wide methylation in gliomas

Abstract: High-grade gliomas (HGG) are the most common brain tumors, with an average survival time of 14 months. A glioma-CpG island methylator phenotype (G-CIMP), associated with better clinical outcome, has been described in low and high-grade gliomas. Mutation of IDH1 is known to drive the G-CIMP status. In some cases, however, the hypermethylation phenotype is independent of IDH1 mutation, suggesting the involvement of other mechanisms. Here, we demonstrate that DNMT1 expression is higher in low-grade gliomas compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…The JNK pathway is a possible delayed pathway that is activated in 10% O 2 in light of our previous study [14]. Also, there was research showing that JNK signaling may contribute to Snail and TWIST1 activation by DNA methyltransferase 1 (DNMT1) or TGF-β1-induced EMT pathway by promoting fibronectin and vimentin [21][22][23][24][25][26][27]. Our results demonstrated the general activation through hyperphosphorylation under low oxygen levels among all three cell lines, and this confirmed the activation of JNK pathway among CRCs.…”
Section: Discussionmentioning
confidence: 79%
“…The JNK pathway is a possible delayed pathway that is activated in 10% O 2 in light of our previous study [14]. Also, there was research showing that JNK signaling may contribute to Snail and TWIST1 activation by DNA methyltransferase 1 (DNMT1) or TGF-β1-induced EMT pathway by promoting fibronectin and vimentin [21][22][23][24][25][26][27]. Our results demonstrated the general activation through hyperphosphorylation under low oxygen levels among all three cell lines, and this confirmed the activation of JNK pathway among CRCs.…”
Section: Discussionmentioning
confidence: 79%
“…In recent work with murine cells, oncogenic Ras signaling has been shown to induce transcriptional changes leading to an accumulation of H3K27me3 and to mediate upregulation of Dnmt1 and Dnmt3a expression, which provides a molecular link for RAS-mediated transcriptional silencing and DNA hypermethylation 45 47 . Furthermore, it has been shown that phosphorylated c-Jun, which is regulated in a RAS-dependent manner, upregulates DNMT1 expression and causes DNA hypermethylation 48 . Oncogenic KRAS is also able to suppress the expression of TET1 in an ERK-dependent manner, thereby contributing to DNA hypermethylation 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In earlier studies, JNK phosphorylation is found to mediate TGF-β1-induced EMT by promoting fibronectin and vimentin synthesis in fibroblasts and keratinocytes (114)(115)(116). Additionally, JNK activation of the proliferating cell nuclear antigen (PCNA) and DNA methyltransferase 1 associated protein 1 (DMAP1) domains of DNA methyltransferase 1 (DNMT1) can directly interact with Snail and suppress E-cadherin in colorectal cancer, glioma, and nasopharyngeal carcinoma cell lines (117)(118)(119). Furthermore, JNK may be associated with Snail and TWIST1 via c-Jun in multi-drug resistant epidermoid carcinoma and as a downstream effector of Akt in gastric cancer cells (120,121).…”
Section: Mapksmentioning
confidence: 96%